ChemInform Abstract: Cu(I)‐Catalyzed Synthesis of N‐Tosyl‐4‐iminoquinolizines. Issue 41 (October 2015) - Chen, Joanna L.; Namirembe, Sheila; Lauchert, Luke T.; Tsougranis, Gregory H.; Isaacs, Andre K.
Abstract Ketenimines generated in situ from 2‐pyridyl compounds and azide (II) undergo an intramolecular cyclization reaction to yield iminoquinolizines.